The Emotional Impacts of Working as an Asylum Lawyer. (16th January 2019) - Graffin, Neil
Abstract: Asylum practitioners often work with traumatised persons and hear stories of persecution and other traumatic narratives in their everyday work. This study sought to assess the emotional impacts of working as an asylum practitioner, and how these effects could affect a practitioner's performance in their role or their relationship with their clients. This qualitative study consisted of 10 semi-structured interviews with asylum practitioners in England and the Republic of Ireland. An inductive thematic analysis was used to analyse data. A number of key themes emerged, including participants describing having experienced or witnessed burnout and other negative emotional effects caused by working in this role. Practitioners also described having experienced feelings of detachment from clients, as well as in some cases cynicism and disbelief of their narratives. However, these emotional states were seen to engender positive as well as negative attributes in the delivery of legal representation. Heavy caseloads, the futility of working in a system where some clients have little chance of success, cuts to legal aid, as well as societal stigmatisation of claimants were also cited as providing challenges for practitioners. A complex understanding of this role emerged in times of austerity, where anti-immigration sentiment is common within society.